Етапи формування термінальної хвороби лівого передсердя: понад 20-річне клінічне спостереження та вибір лікувальної тактики - L. I. Vasilyeva; O. S. Kalashnikova (Ukrainian Heart Journal, 2026)
The aim – to analyze the stages of calcified left atrial disease formation based on more than 20 years of clinical follow-up, to assess its clinical, hemodynamic, and morphological manifestations, and to determine its role in the development of pulmonary hypertension and in guiding therapeutic and transplantation strategies.Materials and methods. A retrospective analysis was performed based on data from more than 20 years of prospective follow-up of a patient with hypertrophic cardiomyopathy, subaortic membrane, and long-standing persistent atrial fibrillation who underwent repeated catheter interventions and surgical treatment. Structural and functional cardiac changes were assessed using multimodality imaging (echocardiography, including speckle-tracking, multislice computed tomography, cardiac magnetic resonance imaging), as well as right heart catheterization.Results. Long-term follow-up demonstrated a stepwise evolution of left atrial disease – from functional impairment of compliance and mechanical dysfunction to the development of advanced structural remodeling with diffuse wall calcification. Despite relief of left ventricular outflow tract obstruction and rhythm control, the later stages were characterized by progressive elevation of pulmonary artery pressure, right heart chamber dilation, and development of severe right ventricular failure. At this stage, calcified left atrial disease emerged as a dominant pathogenic factor driving the development of combined pulmonary hypertension.Conclusions. Calcified left atrial disease represents the terminal stage of atrial remodeling and may determine the development of severe pulmonary hypertension and right ventricular failure regardless of the underlying left ventricular pathology. Early identification of structural and functional abnormalities of the left atrium is crucial for risk stratification and timely modification of therapeutic strategy – from correction of hemodynamic and arrhythmic factors to evaluation of indications for heart–lung transplantation.